Jewish philosophy A-Z - Hughes, Aaron W., 1968- (Philosophy A-Z series., 2005)
This volume covers the major traditions of thought from Philo to Levinas and, since Jewish philosophy has occurred in broader environments (e.g., Hellenistic Alexandria, Medieval Baghdad, Weimar Germany), non-Jewish thinkers who have had an important influence on Jewish philosophy are also included (e.g., Plotinus, Alfarabi, Heidegger).